Understanding the Roles and Challenges of Local Government in the Era of Technological Transformation in Indonesia: A Study of Public Policy Literacy - Yeti Rohayati; B.M.A.S. Anaconda Bangkara; Egidius Fkun; Ade Iskandar; Jufri Jacob (Universitas Muhammadiyah Ponorogo, 2022)
This study is aimed to understand the challenges of the Indonesia’s local governments in the era where technology has transformed the public service system from a manual method to an all-digital application method. A series of efforts are made to discuss and find the solutions to the problem of the study. The data is searched electronically from literature sources including various publications such as journals, and other papers that are used as the data sources of this research. After a series of selection and searching for relevant data, the required data is finally collected. The data is examined through a phenomenological approach, referring to an effort in obtaining resilience from some existing data to get the answers for the discussed phenomenon, the challenges and roles of local government. The analysis process involves several techniques, including coding, verifying, evaluating, synthesizing, organizing, and carrying out in-depth interpretations that make it easier for the author to draw conclusions to answer the research problem with a good validity. The results of the data and discussion conclude that the challenges and roles given to the local governments in this reform era include the inconsistency of Bureaucratic Reform in the government and the challenges in adapting various dynamics such as pandemics and other crises, including the abuse of authority and indiscipline of the apparatus, especially the officials in carrying out their duties and functions as public servants. Thus, this research provides important results that complements and enlightens similar researches in the future.